2022
DOI: 10.3390/ijerph19138053
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth Targets and Carbon Emissions: Evidence from China

Abstract: Carbon emissions have become a new threat to sustainable development in China, and local government actions can play an important role in energy conservation and emission reduction. This paper explores the theoretical mechanisms and transmission paths of economic growth targets affecting carbon emissions from the perspective of economic growth targets and conducts an empirical analysis based on 30 provincial panel data in China from 2003 to 2019. The results show that: economic growth targets are positively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 64 publications
(86 reference statements)
2
13
0
Order By: Relevance
“…Its primary goal is to promote the transformation and upgrading of industrial civilization to ecological civilization [ 8 ]. However, the transition from brown economy to green economy will involve government policies [ 9 , 10 ], economic growth target pressure [ 11 , 12 ], technological progress [ 13 ], socio-cultural contexts [ 14 ], transition costs [ 15 , 16 , 17 ], and many other factors. Among many potential factors affecting green growth, human capital, known as a kind of living capital, refers to the knowledge and skill sets that workers have [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its primary goal is to promote the transformation and upgrading of industrial civilization to ecological civilization [ 8 ]. However, the transition from brown economy to green economy will involve government policies [ 9 , 10 ], economic growth target pressure [ 11 , 12 ], technological progress [ 13 ], socio-cultural contexts [ 14 ], transition costs [ 15 , 16 , 17 ], and many other factors. Among many potential factors affecting green growth, human capital, known as a kind of living capital, refers to the knowledge and skill sets that workers have [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial transformation will be critical for sustainable development and the successful realization of CO2 emissions reduction (Zhang et al, 2019). Many scholars believe that accelerating the upgrading of industrial structure will help to alleviate carbon emissions and mitigate the greenhouse effect (Zhao et al, 2022). Yu et al (2018)also supported this negative industrial structure transformation and CO2 nexus by using the ridge regression method.…”
Section: Impact Of Industrial Structure Upgrading On Carbon Emissionmentioning
confidence: 99%
“…Unfortunately, the empirical results showed that the combined effect of industrial structure optimization and technical progress on reducing carbon intensity was not significant. Zhao et al (2022) explored the impact of industrial structure upgrading on carbon emissions based on a spatial and mediating effect model. The study showed that industrial structure upgrading could alleviate carbon emissions in the region, and also contribute to energy conservation and emission reduction in neighboring regions.…”
Section: Impact Of Industrial Structure Upgrading On Carbon Emissionmentioning
confidence: 99%
“…In response to severe environmental problems and challenges, the Chinese government has proposed the strategic deployment of “Promoting green development and accelerating the establishment of ecological civilization” in the report of the 19th National Congress, and the 14th Five-Year Plan further clarifies that it is compulsory to support green technology innovation and promote cleaner production. Strengthening environmental governance and promoting green and sustainable development have become a consensus in society [ 4 , 5 ]. In the same manner, the government of China has promulgated and implemented several environmental management policies and initiatives and has gradually strengthened environmental regulations with a view to enhancing environmental performance and achieving green development.…”
Section: Introductionmentioning
confidence: 99%